Proof without words: Knopp series for (pi) - Plaza, Ángel (Teaching Mathematics and Computer Science, 2006)
There are many expressions for number π as infinite series or infinite product (see for example [1, 2, 3]). In [1] the following series for number π is attributed to K. Knopp:...